OSI MODEL Data link & Physical Layer - Eldrnawi, Mona (Libyan International Medical University - Faculty of Information Technology, 2022)
The data link layer, is concerned with packaging data into frames and transmitting those frames on the network, performing error detection/ correction, uniquely identifying network devices with an address, and handling flow control. These processes are collectively referred to as data-link control (DLC). The physical layer, is concerned with the transmission of bits on the network along with the physical and electrical characteristics of the network.